1998
DOI: 10.1016/s0378-1097(98)00025-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic DNA fingerprinting of clinical isolates of Helicobacter pylori by REP-PCR and restriction fragment end-labelling

Abstract: Genetic diversity of 32 Helicobacter pylori strains isolated from patients with gastritis, gastric or duodenal ulcer, carcinoma, or lymphoma was determined by repetitive sequence element polymerase chain reaction (REP-PCR), and by the new typing method restriction fragment end-labelling (RFEL). Furthermore, these two methods were used to investigate a possible correlation between clinical symptoms and the genetic background of Helicobacter pylori. Both REP-PCR and RFEL revealed 31 different patterns for the 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
20
1
Order By: Relevance
“…REP-PCR typing has generated stable, reproducible DNA fingerprints that have been successfully used to discriminate H. pylori strains associated with PUD in a U.S. study (7), but this was not confirmed in a European study (16). The results from the present study suggest that REP fingerprints may be useful for defining disease-associated strains in a recent bacterial population derived from mixed population groups (European, Southeast Asian, and African).…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…REP-PCR typing has generated stable, reproducible DNA fingerprints that have been successfully used to discriminate H. pylori strains associated with PUD in a U.S. study (7), but this was not confirmed in a European study (16). The results from the present study suggest that REP fingerprints may be useful for defining disease-associated strains in a recent bacterial population derived from mixed population groups (European, Southeast Asian, and African).…”
Section: Discussioncontrasting
confidence: 61%
“…The REP-and RAPD-PCR fingerprints of the H. pylori strains were analyzed with GelCompar software, Windows version 4.1 (Applied Math, Kortrijk, Belgium) (16). Both REP-and RAPD-PCR patterns were normalized using the 0.1-kbp molecular size standard.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations